Laporan hasil Seminar Pendidikan Agama Islam dan Pendidikan Pancasila (Sub Proyek Pembinaan Mata Kuliah Dasar Umum, 1982)
On development of moral education and national awareness according to Islam and Pancasila; seminar papers.